2004
DOI: 10.1207/s15430154jce1901_13
|View full text |Cite
|
Sign up to set email alerts
|

To Refer or Not to Refer: Factors that Affect Primary Care Provider Referral of Patients with Cancer to Clinical Treatment Trials

Abstract: Findings support allocating funds to provide CCTT education to PCPs to increase numbers of patients willing to participate in CCTTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…3), whereas 3 studies found provider attitudes to be a promoter of patient accrual. 18,20,26 The studies also reported that provider attitudes toward patient age, 11,12,16,17 comorbidities, 12,16,17 and disease stage, 16 physician perception of patient mistrust of researchers, 14,25 and lack of physician awareness about trials 14,23,25 were factors that prevented providers from enrolling their patients into clinical trials.…”
Section: Provider Barriers and Promotersmentioning
confidence: 99%
See 2 more Smart Citations
“…3), whereas 3 studies found provider attitudes to be a promoter of patient accrual. 18,20,26 The studies also reported that provider attitudes toward patient age, 11,12,16,17 comorbidities, 12,16,17 and disease stage, 16 physician perception of patient mistrust of researchers, 14,25 and lack of physician awareness about trials 14,23,25 were factors that prevented providers from enrolling their patients into clinical trials.…”
Section: Provider Barriers and Promotersmentioning
confidence: 99%
“…Of the 18 studies eligible for review, 3 were published before 1993, 10-12 2 were published between 1993 and 1999, 13,14 and 13 were published in 2000 or later (Table 1). [15][16][17][18][19][20][21][22][23][24][25][26][27] The study designs included a randomized controlled trial (n ¼ 1), concurrent controlled trial (n ¼ 1), casecontrol (n ¼ 1), and descriptive (n ¼ 15), with 4 of the studies also using qualitative techniques to facilitate in-depth assessments of physician attitudes and perceptions. Fourteen studies reported recruitment into treatment trials only [10][11][12][13][15][16][17][18][19][20][21][22]24,26 ; 3 studies reported recruitment into both prevention and treatment trials 14,25,27 ; and 1 study reported recruitment to a prevention trial (Table 1).…”
Section: Yield Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…20 This engagement of primary care providers in CT marketing appears to be underused; an NCI survey of primary care providers revealed that 98% did not discuss CTs with their patients and 37% were unaware that CTs might be an option. 21,22 Unpublished data from the Gordon et al study asked the primary care provider respondents about their awareness of and comfort with CTs. Seventy-eight percent thought the upper age limit for inclusion in NCIsponsored pediatric oncology trials was #21 years; only 14% felt more than moderately confident introducing CTs, and 65% felt it was not within their job scope (L.M.…”
Section: Influencing Referral Of Ayas To Centers With High Ct Accrualsmentioning
confidence: 99%
“…Surgeons often have several contacts with patients, and frequently discuss possible treatments before the patient's first visit to a medical or radiation oncologist. Because trust in a physician, particularly when the physician recommends a clinical trial, has been noted to be highly associated with trial recruitment [10][11][12][13][14][15] , we decided to undertake a prospective exploratory pilot study to evaluate whether specific referring surgeon-initiated interventions aimed at reducing physician and patient barriers could enhance clinical trial accrual in breast cancer patients. Accrual to clinical trials is a multidimensional problem that requires multidimensional interventions to effect improvement, and the potential influence of the referring surgeon is one dimension emphasized in the present study.…”
Section: Introductionmentioning
confidence: 99%